Abdominal wall endometriosis in patients with a history of cesarian section - (:unkn) unknown (EDIZIONI LUIGI POZZI, 2018)
OBJECTIVE: The aim of this study is to review the characteristics, intraoperative and radiological findings of abdominal wall endometriosis (AWE). METHODS: This retrospective observational cohort study was executed through analysis of the medical records of patients who underwent excision of AWE between January 2000 and June 2017. All the diagnoses were confirmed pathologically. Characteristics, intraoperative and radiological findings of patients with AWE were and analyzed. RESULTS: Each of the 20 patients had a history of at least one prior cesarean section. The main presenting symptoms were pain (70%). Ultrasonography and/or magnetic resonance imaging was performed in 95% and 45 % of the patients, respectively. One patient (5%) was investigated by 18 Fluorodeoxyglucose positron emission tomography - computed tomography. The preoperative radiological diagnosis was correcting in 55 % of the cases. The mean diameter of the masses was 4.7 +/- 1.53 cm. Recurrence was found only in one patient during 36-month follow-up. DISCUSSION: Meticulous anamnesis, accurate clinical examination and proper imaging studies, are important guides for diagnosis. CONCLUSION: AWE should be kept in mind when pain or mass is detected on the abdominal wall of women who have cesarean section history.
Keywords: Abdominal wall endometriosis; Cesarean section; Radiology; Scar endometriosis; SCAR ENDOMETRIOSIS; SURGICAL SCAR; RISK